2004
DOI: 10.1136/sti.2004.010850
|View full text |Cite
|
Sign up to set email alerts
|

Risk of undiagnosed infection in men attending a sexual assault referral centre

Abstract: Objectives: To investigate men undergoing forensic examination at the Haven, a specialist centre for the management of sexual assault in south London. Methods: Forensic notes of 92 men attending the Haven from May 2000 to August 2003 were identified and a detailed review performed. Results: Males ranged in age from 12 to 51 years, with 83% within the range 12-35 years. 78% were white. Of those who were sexually active (n = 82) 30% were heterosexual, 34% were homosexual, and the remainder provided no informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Internationally, two single-site studies found less than 10% of patients accepted the nPEP offer (Kerr, Cottee, Chowdhury, Jawad, & Welch, 2003;Templeton, Davies, Garvin, & Garsia, 2005). Acceptance by 20-60% of patients offered nPEP was found in three additional single-site studies (Diniz, Almeida, Ribeiro, & Macedo, 2007;Reeves, Jawad, & Welch, 2004;Wiebe, Comay, McGregor, & Ducceschi, 2000). And acceptance greater than 80% was found in the remaining four studies; two conducted at single sites (Garcia et al, 2005;Limb, Kawsar, & Forster, 2002), one inclusive of city-wide data (Sonder et al, 2007), and one regional (Carrieri, Bendiane, Moatti, & Rey, 2006).…”
Section: Npep Acceptancementioning
confidence: 92%
See 4 more Smart Citations
“…Internationally, two single-site studies found less than 10% of patients accepted the nPEP offer (Kerr, Cottee, Chowdhury, Jawad, & Welch, 2003;Templeton, Davies, Garvin, & Garsia, 2005). Acceptance by 20-60% of patients offered nPEP was found in three additional single-site studies (Diniz, Almeida, Ribeiro, & Macedo, 2007;Reeves, Jawad, & Welch, 2004;Wiebe, Comay, McGregor, & Ducceschi, 2000). And acceptance greater than 80% was found in the remaining four studies; two conducted at single sites (Garcia et al, 2005;Limb, Kawsar, & Forster, 2002), one inclusive of city-wide data (Sonder et al, 2007), and one regional (Carrieri, Bendiane, Moatti, & Rey, 2006).…”
Section: Npep Acceptancementioning
confidence: 92%
“…Rates of nPEP acceptance for the remaining four US adult populations ranged from moderate (20-40%) in one state-wide, and one single-site study (Merchant et al, 2008;Myles, Hirozawa, Katz, Kimmerling, & Bamberger, 2000) to greater than 75% in two other single-site studies (Linden et al, 2005;Merchant et al, 2003). In the four studies concurrent to CDC (2005) guideline publication (see Table 5), Diniz et al (2007) 92 52 (57%) Garcia et al (2005) 278 169 (60%) Kerr et al (2003) 34 14 (41%) Limb et al (2002) 8 5 (63%) Reeves et al (2004) 31 3 (9%) Rey et al (2008) -53 (54%) Sonder et al (2007) 23 - Templeton et al (2005) 9 3 (30%) Wiebe et al (2000) 71 8 (11%) Studies with US populations conducted pre-CDC guidelines Linden et al (2005) 82 18 (22%) Merchant et al (2008) 35 - Merchant et al (2003) 34 - Moe and Grau (2001) 2 - Myles et al (2000) 69 26 (28%) Completed 1 week Pesola et al (1999) 2 - Straight and Heaton (2007) 846 -Note: xUnless otherwise noted. *Percentage reflects the number completing nPEP out of those who accepted nPEP.…”
Section: Npep Acceptancementioning
confidence: 94%
See 3 more Smart Citations